Finland : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Selected Issues paper examines Finland's sectoral balance sheets and how they have evolved since the global financial crisis; the analysis reveals that financial vulnerabilities have risen in most sectors. Indebtedness has increased for nonfinancial corporations (NFCs), households, and the government, increasing their financial fragility and vulnerability to shocks. Also, cross-border financial exposures have risen on both sides of Finland's balance sheet. Specifically, banks' balance sheets have grown considerably, largely owing to a rise in foreign liabilities. NFCs and the government have also relied in part on foreign investors to finance their debt increases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet